PENERAPAN MEDIA PEMBELAJARAN GENIALLY TERHADAP HASIL BELAJAR SISWA PADA PELAJARAN INFORMATIKA - Imran Jamaluddin; Yoyo Zakaria (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of using Genially-based interactive learning media on the learning outcomes of seventh-grade students in the Informatics subject at SMP IT Mumtaz Islamic School, particularly on Information Systems material. An experimental method with a One Group Pretest-Posttest Design was applied to 20 students. Data were gathered through a 20-item multiple-choice test and validation questionnaires completed by a media expert, a material expert, and the Informatics teacher. The average pretest score of 57.00 rose to 82.75 at posttest, yielding an N-Gain of 0.58 (57.76%), classified as moderate. The data were normally distributed (Shapiro-Wilk) and homogeneous (Levene), and the Paired Sample t-Test produced a t-value of 6.43, exceeding the t-table value of 2.042, so H0 was rejected and H1 accepted. Expert validation placed the media in the Very Feasible category, with scores of 92.50% (media expert), 90.00% (material expert), and 97.50% (teacher effectiveness). These findings indicate that Genially-based interactive learning media significantly improves students' learning outcomes in Informatics, although the absence of a control group and the small sample size mean the results should be read as preliminary evidence requiring further testing.